Discovery of 3, 4-dihydrobenzo[f][1, 4]oxazepin-5(2H)-one derivatives as a new class of ROCK inhibitors for the treatment of glaucoma. (1st August 2021) - Sun, Yumeng; Li, Yueshan; Miao, Zhuang; Yang, Ruicheng; Zhang, Yun; Wu, Ming; Lin, Guifeng; Li, Linli
Graphical abstract: Highlights: A novel class of ROCK inhibitors was reported. Compound 12b showed good selectivity and potent activity against ROCK I and II. 12b was proved to be a promising lead compound of anti-glaucoma. Abstract: The Rho-associated protein kinases (ROCKs) are associated with the pathology of glaucoma and discovery of ROCK inhibitors has attracted much attention in recent years. Herein, we report a series of 3, 4-dihydrobenzo[ f ][1, 4]oxazepin-5(2 H )-one derivatives as a new class of ROCK inhibitors. Structure-activity relationship studies led to the discovery of compound 12b, which showed potent activities against ROCK I and ROCK Ⅱ with IC50 values of 93 nM and 3 nM, respectively. 12b also displayed considerable selectivity for ROCKs. The mean IOP-lowering effect of 12b in an ocular normotensive model was 34.3%, and no obvious hyperemia was observed. Overall, this study provides a good starting point for ROCK-targeting drug discovery against glaucoma.